David Fincher mind games - Nayman, Adam (Abrams, 2021)
David Fincher: Mind Games' is the definitive critical and visual survey of the Academy Award- and Golden Globe-nominated works of director David Fincher. From feature films Alien 3, Se7en, The Game, Fight Club, Panic Room, Zodiac, The Curious Case of Benjamin Button, The Social Network, The Girl With the Dragon Tattoo, Gone Girl, and Mank through his MTV clips for Madonna and the Rolling Stones and the Netflix series House of Cards and Mindhunter, each chapter weaves production history with original critical analysis, as well as with behind the scenes photography, still-frames, and original illustrations from Little White Lies' international team of artists and graphic designers. Mind Games also features interviews with Fincher's frequent collaborators, including Jeff Cronenweth, Angus Wall, Laray Mayfield, Holt McCallany, Howard Shore and Erik Messerschmidt. Grouping Fincher's work around themes of procedure, imprisonment, paranoia, prestige and relationship dynamics, Mind Games is styled as an investigation into a filmmaker obsessed with investigation, and the design will shift to echo case files within a larger psychological profile
Keywords: Fincher, David -- 1962-; Biography & Memoir; Performing arts; Fincher, David / Criticism and interpretation; Motion pictures / United States / History and criticism / 20th century; Motion picture producers and directors / United States / Biography; Motion pictures / United States / Reviews; Fincher, David / https://isni.org/isni/0000000120234275; Fincher, David; Motion pictures; Motion picture producers and directors; United States; 1900-1999; Reviews; Criticism, interpretation, etc; Biographies